PENGARUH ONLINE CUSTOMER REVIEW, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK HAND AND BODY LOTION VASELINE (Studi Kasus Pada Konsumen Hand and Body Lotion Vaseline Di Solo Raya) - Findi wahyu utami; Budi istiyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Business opportunities in the beauty industry are increasingly wide open. However, based on facts on the ground, Vaseline has sufficiently mastered the existing opportunities, because the brand's position is currently experiencing improvement. This fact was taken based on the results of the 2020 - 2023 Top Brand Awards which showed that Vaseline was included in the Top Brand Awards in 2023. The aim of this research is to find out how online customer reviews, price and brand image influence the purchasing decisions of Solo Raya consumers. This examination strategy uses quantitative techniques. The population in this study is not limited to young people in Solo Raya who use Vaseline Hand and Body Cream. The examination strategy used is non probability sampling with a purposive sampling testing method. The sample obtained was 80 respondents who used Vaseline body lotion. The information used is important information obtained from distributing opinion questionnaires with a Likert scale. The information checking strategy uses data tests, classical instrument tests, multiple regression analysis, and various direct relapse investigations, f tests, t tests, collateral coefficients using the SPSS application. The further impact of this exploration shows that the online customer review variable has no influence on purchasing choices, while price and brand image influence purchasing decisions.